Breakdown characteristics and dielectric properties of palm oil and coconut oil based tio2 nanofluids - Mohd Nor, Shamsul Fahmi (2016)
The increasing concerns on environmental issues have led to the introduction of vegetable oils such as Palm Oil (PO) and Coconut Oil (CO) as potential candidates for alternative dielectric insulating fluids for mineral oil. Even though the overall performances of these oils are comparable with other types of vegetable oils, some improvements can be carried out especially on their electrical properties. Extensive electrical examinations need to be conducted on these PO and CO at laboratory level in order to determine its feasibility for practical application in transformers. This work presents an examination on the electrical properties of PO and CO under the presence of a semi-conductive nanoparticle, Titanium (IV) Oxide (TiO2). Refined, Bleached and Deodorized Palm Oil (RBDPO) Olein was used in this study, whereas the volume concentrations of TiO2 used are from 0.001% to 0.050%. Investigation on the effects of a surfactant, Cetrimonium Bromide (CTAB) was also carried out. Transmission Electron Microscope (TEM) was used to examine the morphology of RBDPO and CO based TiO2 nanofluid. Moreover, AC and lightning breakdown voltages, dielectric dissipation factor, relative permittivity and resistivity measurements were taken whereas the withstand voltages for AC and lightning were statistically evaluated through Weibull distribution. This study found that the AC breakdown voltages of the RBDPO and CO can be increased through introduction of TiO2 without CTAB where the highest percentages of increments are 17.2% and 22.7% respectively. The AC breakdown voltage of RBDPO and CO based TiO2 nanofluid can however decrease with introduction of CTAB. The effect of TiO2 on the lightning breakdown voltages of RBDPO and CO under both fields is quite small for samples with or without CTAB where the highest percentages of increments are 9.2% and 11.3% respectively. The dielectric dissipation factors and resistivity of RBDPO and CO based TiO2 nanofluid are significantly affected by the presence of CTAB whereas TiO2 has no significant effect on the relative permittivity of RBDPO and CO for samples with and without CTAB. The statistical analysis reveal that the AC breakdown voltages at 1% probability for RBDPO and CO have experienced a significant improvement after the introduction of TiO2 regardless with or without CTAB where the highest percentages of increments are 63.9% and 36.8% respectively. On the other hand, TiO2 has small effect on improving the lightning breakdown voltages at 1% probability under non-uniform field regardless with or without CTAB. Significant improvements of the lightning breakdown voltages at 1% probability under quasi uniform field are found for samples with CTAB.